ANGIOSARCOMA OF THE HEART - Luper, William E. (1977)
A case of primary angiosarcoma arising in the right atrium is described. The clinical, pathological, therapeutic and prognostic features are discussed. A review of the literature reveals 52 cases to date, including the present case.